Mula pabrika hanggang Fukuoka - Carolino, Ditsi; Buxani, Sadhana (Ateneo Center for Social Policy and Public Affairs, 1999)
A three-part documentary about Filipina women and work. Elsa in rural Luzon works long hours in a garment sweatshop and spends the night on the picketline. In Tokyo, artist Veng seeks various work while pursuing her interests in photography and filmmaking. In Fukuoka, three Filipinas married to Japanese men reveal their stories as entertainers.